Effects of adding radicchio (Cichorium intybus L.) powder to rice cakes (Sulgidduk) on the quality - O, Hyeonbin; Song, Ka-Young; Zhang, Yangyang; Kim, Young-Soon (Progress in Nutrition, 2018)
This study investigated the quality, antioxidant activities, and sensory properties of Sulgidduk (rice cakes) upon the addition of radicchio (Cichorium intybus L.) powder, which is known to have antioxidant and anti-diabetic effects. Radicchio powder was freeze-dried, passed through a 40-mesh sieve, and used to replace 0%, 0.5%, 1%, 2%, 3%, or 4% of the rice flour. The content of moisture in Sulgidduk did not significantly differ among samples (p<0.05). As the amount of radicchio powder increased, the pH value decreased slightly. Regarding color, the L-value decreased from 84.44 (control) to 45.91 (4% sample), and the a-value increased from -1.16 (control) to 5.20 (4% sample). The b-value increased from control to 2% samples, but then gradually decreased in the 3% and 4% samples. Though hardness and chewiness increased upon adding radicchio powder, the springiness and cohesiveness of the radicchio Sulgidduk samples were reduced when compared to these of the control samples (84.43% and 78.17%, respectively). Antioxidant activity of Sulgidduk increased significantly upon the addition of radicchio. For sensory evaluation, the 1% sample received the highest score (5.35) in overall acceptability. From these results, we determine that addition of 1% radicchio powder to Sulgidduk is suitable for producing the rice cake.